1980
DOI: 10.1021/np50009a002
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Metabolites. VIII: Structures of New Sesquiterpenes From Lactarius Scrobiculatus

Abstract: GIORGIO MELLERIO', GIOI-ASSI T-IDARI* and P.io~.i I-ITA-FISSI~ * ?Isfituto di Chiniica Organicci--ni;,ersita degli Studi-lCale W r a n i e l l i 10-27100 PaLmia (Italy) 3Centro del C-TR p e r lo Studio delle Sostanre Organiche .\htiirali-Politecnico-Piarra L e o m r d o do Ti'nci 32-20133 X i l a n o (Italjj ;iBsTR.icT.-From lots of Lncfarrzts scrobzciilnfus extracted in different B-ays, in addition to ethyl linoleate and cerevisterol, nine lactarane sesquiterpenes have been isolated. The main compounds are fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The chemical shift of C-4, C-6, C-10 suggested that these carbons were oxygen substituted. The 1 H NMR spectrum of 2 showed the presence of two secondary methyl groups at δ 0.97 (d, J = 6.6 Hz), 1.02 (d, J = 6.6 Hz), two tertiary methyl groups at δ 1.11 (s), 1.20 (s), and an ethoxy group at 1.11 (t, J = 7.0 Hz), δ 3.27 (1H, dq, J = 9.0, 7.0 Hz), 3.40 (1H, dq, J = 9.0, 7.0 Hz) [13], which explained the presence of two carbon atoms extra to a bicyclic sesquiterpene skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shift of C-4, C-6, C-10 suggested that these carbons were oxygen substituted. The 1 H NMR spectrum of 2 showed the presence of two secondary methyl groups at δ 0.97 (d, J = 6.6 Hz), 1.02 (d, J = 6.6 Hz), two tertiary methyl groups at δ 1.11 (s), 1.20 (s), and an ethoxy group at 1.11 (t, J = 7.0 Hz), δ 3.27 (1H, dq, J = 9.0, 7.0 Hz), 3.40 (1H, dq, J = 9.0, 7.0 Hz) [13], which explained the presence of two carbon atoms extra to a bicyclic sesquiterpene skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…178 2.5.1.3 Lactaranes. Diverse types of lactarane sesquiterpenes have been identied from the Russulaceae family of fungi (genera Lactarius and Russula), [182][183][184][185][186][187][188][189] particularly from the poisonous mushroom Lactarius scrobiculatus, which has an intensely pungent taste presumed to be responsible for the high toxicity of the mushroom. Among different types, sesquiterpene lactones account for the majority of lactaranetype lactones.…”
Section: Reviewmentioning
confidence: 99%
“…The condensation product 34 has been detected when acetone has been used in the extraction. 41,51 In studies on the carotenoids from the bacterium Rhodopseudomonas viridis, the condensation product of lycopene 20-aldehyde with acetone was also detected 52 as an artefact when acetone was used during the extraction. The purification of the diterpenoid quinones from Plectranthus grandidentus using acetone afforded 53 some unusual artefacts including 35 involving the addition of acetone.…”
Section: 4mentioning
confidence: 99%